2021
DOI: 10.1097/icu.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic keratopathy and refractive surgery

Abstract: Purpose of reviewCorneal nerve function is an important consideration for the refractive surgeon. In patients without a history of neuropathy, refractive surgery can lead to destruction of corneal nerves and may predispose to keratopathy. The purpose of this review is to provide an update on the effect of refractive surgery on corneal nerve function and the potential for an increased risk of neurotrophic keratopathy development. Recent findingsRecent studies have reinforced that refractive surgery can cause an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are some limitations in this study, including the relatively short duration of postsurgical follow-up. Cross-sectional studies have reported the onset of persistent ocular symptoms to range from immediately following surgery to as long as several years later . As the present study continues, we plan to analyze reports from participants after longer postoperative periods.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are some limitations in this study, including the relatively short duration of postsurgical follow-up. Cross-sectional studies have reported the onset of persistent ocular symptoms to range from immediately following surgery to as long as several years later . As the present study continues, we plan to analyze reports from participants after longer postoperative periods.…”
Section: Discussionmentioning
confidence: 94%
“…Crosssectional studies have reported the onset of persistent ocular symptoms to range from immediately following surgery to as long as several years later. 54 As the present study continues, we plan to analyze reports from participants after longer postoperative periods. Another limitation is the modest sample size; however, the relatively low incidence of persistent pain and the prospective nature of the study limited the number of qualified participants.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In certain cases, the complete removal of a tumor without causing harm to vital nerves or adjacent structures necessitates the use of highly sophisticated surgical techniques [ 3 ]. Damage to important nerves or structures during surgery can result in postoperative functional impairments or complications [ 4 ]. Although the BNST is considered benign, it is still important to acknowledge the possibility of local recurrence, necessitating close follow-up [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology mechanism of post FS-LASIK dry eye is mainly associated with damage to corneal nerve fibers and ocular surface tissues ( 1 ). Most dry eye symptoms disappear within 6–9 months after surgery as corneal nerve regenerates ( 2 , 3 ). However, we should be aware that patients may still suffer from dry eye in the recovery period.…”
Section: Introductionmentioning
confidence: 99%